Method for analyzing working state of aqueous zinc ion battery

By combining inductively coupled plasma mass spectrometry and time-of-flight secondary ion mass spectrometry technology, the working state of the aqueous zinc ion battery is analyzed, which solves the problem that the existing technology is difficult to effectively detect the working state of the battery, and realizes real-time and accurate battery state detection and analysis.

CN119688818AActive Publication Date: 2025-03-25FUZHOU UNIV
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411927896.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-03-25
Estimated Expiration
2044-12-25

AI Technical Summary

Technical Problem

The prior art is difficult to effectively detect the working state of the aqueous zinc ion battery, especially in the positive electrode oxidation and reduction reaction, and traditional methods are difficult to observe intuitively, affecting the high life, high stability and wearability of the battery.

Method used

The working state of the aqueous zinc ion battery is analyzed by combining inductively coupled plasma mass spectrometry and time-of-flight secondary ion mass spectrometry. The electrolyte was analyzed by inductively coupled plasma mass spectrometer, and the positive electrode was analyzed by time-of-flight secondary ion mass spectrometer, and the working status detection results of the aqueous zinc ion battery were obtained.

Benefits of technology

Real-time and accurate detection of the working status of the aqueous zinc ion battery can be realized, and the positive electrode component changes with depth, the amount of the positive electrode active substance dissolved in the electrolyte, the electrolyte composition changes and the material attenuation, providing comprehensive analysis results and supporting timely feedback on the battery operating status.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119688818A_ABST
    Figure CN119688818A_ABST
Patent Text Reader

Abstract

The invention discloses a working state analysis method for an aqueous zinc ion battery. The method comprises the following steps: S1, simultaneously carrying out electrolyte analysis and positive electrode analysis on the aqueous zinc ion battery to be detected; the method comprises the following steps: analyzing an electrolyte of the aqueous zinc ion battery in a working state by using an inductively coupled plasma mass spectrometer to obtain an electrolyte analysis result; analyzing the positive electrode of the aqueous zinc ion battery in the working state by using a time-of-flight secondary ion mass spectrometer to obtain a positive electrode analysis result; s2, comprehensively detecting the working state of the aqueous zinc ion battery in real time by combining the electrolyte analysis result and the positive electrode analysis result, and analyzing to obtain a test result; according to the method, the working state of the water-based zinc ion battery is analyzed by combining inductively coupled plasma mass spectrometry and time-of-flight secondary ion mass spectrometry, and the working state of the water-based zinc ion battery can be accurately and effectively detected in real time.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of battery detection, and in particular relates to a method for analyzing the working state of an aqueous zinc ion battery. Background Art

[0002] With the rapid development of society, the consumption of traditional energy has further accelerated the research on clean and renewable energy. Unlike the rapidly developing lithium-ion batteries, zinc-ion batteries (ZIBs) have rapidly emerged in aqueous secondary batteries. Aqueous zinc-ion batteries have higher safety and lower cost than lithium-ion batteries, and higher energy density than lead-acid batteries. As excellent energy storage devices, they can play an important role in the field of mobile energy storage and large-scale power storage sites. However, the detection of the working state of aqueous zinc-ion batteries is still restricted by some factors. In the working state, the positive electrode of aqueous zinc-ion batteries undergoes redox reactions, such as the insertion and extraction of H or Zn, which is difficult to observe intuitively in traditional detection methods. To achieve the high life, high stability and wearability of zinc-ion batteries, more attention must be paid to the detection strategy of the working state of aqueous zinc-ion batteries.

[0003] So far, some strategies for detecting the working status of aqueous zinc-ion batteries have been proposed, such as the detection strategy combining in situ electrochemical mass spectrometry (DEMS) with gas chromatography (GC), the test method combining synchrotron radiation X-ray absorption spectroscopy (XAS) and mass spectrometry (MS), and the characterization method combining in situ optical-Raman-mass spectrometry, etc. However, the test items corresponding to the current analysis process are not comprehensive enough, which affects the process of cause analysis and even leads to the inability to correctly attribute the cause. Summary of the invention

[0004] To solve the above problems, the present invention proposes a method for analyzing the working status of an aqueous zinc ion battery. The method uses a combination of inductively coupled plasma mass spectrometry and time-of-flight secondary ion mass spectrometry to analyze the working status of an aqueous zinc ion battery, which can accurately and effectively detect the working condition of an aqueous zinc ion battery in real time.

[0005] The present invention adopts the following technical solutions:

[0006] A method for analyzing the working state of an aqueous zinc ion battery comprises the following steps:

[0007] S1, performing electrolyte analysis and positive electrode analysis on the aqueous zinc ion battery to be tested at the same time; wherein, the electrolyte of the aqueous zinc ion battery in a working state is analyzed by an inductively coupled plasma mass spectrometer to obtain an electrolyte analysis result; and the positive electrode of the aqueous zinc ion battery in a working state is analyzed by a time-of-flight secondary ion mass spectrometer to obtain a positive electrode analysis result;

[0008] S2. Combine the electrolyte analysis results and the positive electrode analysis results to comprehensively detect the working status of the aqueous zinc ion battery in real time, and analyze the test results.

[0009] Preferably, in step S1, an inductively coupled plasma mass spectrometer is used to instantly detect the element content of the electrolyte during the operation of the aqueous zinc ion battery, and the detected elements include one or more of Zn, Mn, V, Fe, P and S.

[0010] Preferably, in step S1, a time-of-flight secondary ion mass spectrometer is used to instantly detect ion fragments generated by the positive electrode of the aqueous zinc ion battery in operation, and the detected ion fragments include ion fragments of the positive electrode used and by-product ion fragments.

[0011] Preferably, in step S1, before using the inductively coupled plasma mass spectrometer for detection, if the electrolyte is an organic electrolyte or a mixed electrolyte, the electrolyte is first diluted with pure water until the proportion of organic components is less than 10%; if the metal element content in the electrolyte is greater than the threshold value, the sample concentration is diluted between 1 and 10 ppm to improve the test sensitivity.

[0012] Preferably, the specific process of step S2 is: comparing and analyzing the electrolyte analysis results and the positive electrode analysis results, if the content of the main elements of the positive electrode active material in the electrolyte is greater than the threshold value, and the rate at which the percentage of the main ion fragment content of the positive electrode active material decreases with depth is greater than the threshold value, it means that the positive electrode has a high solubility in the electrolyte during the electrochemical process and has a poor recovery ability after a charge and discharge cycle, otherwise it means that the positive electrode has a high solubility in the electrolyte and a good recovery ability; if there are non-initial positive electrode component ion fragments in the positive electrode, it means that there is Zn in the electrochemical work. 2+ and H + The greater the longitudinal depth, the higher the proportion of VO2(B) fragments, indicating that the effective active substances are better maintained; if the percentage of fragments of electrolyte components is high on the surface and the rate of increase with depth is less than the threshold, it means that the electrolyte salt is severely decomposed on the surface.

[0013] After adopting the above technical scheme, the present invention has the following advantages compared with the background technology: the inductively coupled plasma mass spectrometry ICP-MS firstly adopted in the present invention is an inorganic multi-element analysis technology which uses inductively coupled plasma as an ion source and mass spectrometry for detection. ICP-MS uses argon (Ar) plasma, wherein ICP converts the sample into ions, which are then measured using a mass spectrometer (MS); then, the time-of-flight secondary ion mass spectrometry TOF-SIMS adopted is an extremely high-resolution measurement technology which uses primary ions to excite the sample surface, emits extremely small amounts of secondary ions, and measures the mass of the ions according to the different flight times of the secondary ions to the detector due to different masses. The uniqueness of TOF is that the flight time of the ions depends only on their mass. Since a full spectrum can be obtained with one pulse, the ion utilization rate is the highest, and the static analysis of the sample can be best achieved without loss, which is a good characterization method for the positive electrode of the aqueous zinc ion battery in the detection work. Therefore, the method uses inductively coupled plasma mass spectrometry and time-of-flight secondary ion mass spectrometry to analyze the working state of the aqueous zinc ion battery. The battery to be tested can be analyzed in a working state, and the changes in the positive electrode composition with depth, the amount of positive electrode active material dissolved in the electrolyte, the changes in the electrolyte composition and the material attenuation can be confirmed. Through simple tests, the working state of the aqueous zinc ion battery in operation can be comprehensively analyzed, the battery operating state can be accurately obtained, and then a timely response can be made, so that the working condition of the aqueous zinc ion battery can be accurately and effectively detected in real time. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] Figure 1 All fragment spectra obtained by TOF-SIMS testing in the present invention;

[0015] Figure 2 The total number of all fragment counts obtained by TOF-SIMS testing in the present invention;

[0016] Figure 3 This is a graph showing the content variation of the four ion fragments of ZnO-, OH-, VO-, and ZnF2- with the depth of the sample;

[0017] Figure 4 This is a 3D schematic diagram drawn by the present invention using 3Dmax to draw the distribution of the content of four ion fragments ZnO-, OH-, VO-, and ZnF2-. DETAILED DESCRIPTION

[0018] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.

[0019] See also Figures 1 to 4.

[0020] Example 1

[0021] Preparation of aqueous zinc-ion batteries

[0022] A full battery preparation using VO2(B) as the positive electrode active material, water as the solvent, and a 1 mol / L Zn(CF3SO3)2 eutectic electrolyte:

[0023] Preparation of electrolyte: A certain amount of Zn(CF3SO3)2 was added to ultrapure water to prepare an electrolyte with a concentration of 1 mol / LZn(CF3SO3)2.

[0024] Preparation of positive active material: VO2(B) nanorods were prepared by a hydrothermal method. A typical synthesis method adds 3 mmol of V2O5 powder to 30 mL of deionized water and stirs for 10 minutes, then adds 1 mmol of glucose and continues stirring for 10 minutes. The uniform dispersion is then added to a 50 mL Teflon-lined autoclave, heated to 180 ° C and kept for 24 hours to obtain a black powder. After ultrasonic treatment with dimethyl sulfoxide (DMSO), washing with deionized water and ethanol, VO2(B) is obtained by drying at 80 ° C.

[0025] Current collector pretreatment: Stainless steel foil was used as the current collector for the VO2(B) positive electrode. A piece of stainless steel foil with a width of 10 cm was cut from the stainless steel foil roll and the surface and edge of the stainless steel foil were flattened using an electric roller press. The foil was then ultrasonically cleaned with alcohol for 10 minutes, twice.

[0026] Binder preparation: VO2(B) positive electrode uses PVDF as a binder. According to the ratio of 1:25, a certain amount of PVDF and N-methylpyrrolidone are accurately weighed into a beaker, placed on a magnetic stirrer and stirred at a speed of 600 rpm / min to mix evenly.

[0027] Accurately weigh a certain amount of active material VO2 (B), conductive carbon black and binder in a mass ratio of 7:2:1 in a 10ml small beaker and seal it with a sealing film, then add about 4ml N-methylpyrrolidone until the slurry can be stirred normally, and place the prepared slurry on a magnetic stirrer and stir it continuously for 12 hours to obtain a uniformly mixed positive electrode slurry. Then apply the slurry on the pretreated stainless steel foil, and use a four-sided scraper with a gap of 150μm to scrape the slurry at a uniform speed. Place the stainless steel foil with slurry in a vacuum oven at 80℃ and dry it for at least 12 hours. After it is completely cooled to room temperature, take it out, use a battery pole slicer to cut the pole piece according to a diameter of 12mm and place it in a sealed bag in a dryer for later use.

[0028] (3) Negative electrode sheet preparation process: The purchased commercial pure zinc sheet is cut into 10 cm square sheets, and then sent to an electric roller press to flatten the surface and edges of the zinc sheet to a usable thickness of 80 μm. It is placed in an ultrasonic cleaner and cleaned with acetone, ethanol and deionized water respectively. The cleaned zinc sheet is placed in a vacuum drying oven at 60°C and dried for 3 hours. The cooled zinc sheet is taken out and cut into sheets. The diameter of the zinc sheet used directly is cut to 12 mm, and a usable negative electrode sheet is obtained.

[0029] (4) Button cell assembly process: All operations in the button cell assembly process are carried out in an air atmosphere, as described below: 1) Zinc-zinc symmetrical battery: Place the zinc sheet, glass fiber separator, zinc sheet, and stainless steel sheet (SS) in the CR2032 negative electrode battery shell in sequence, then put the spring sheet on, cover the CR2032 positive electrode battery shell, and put it into a button cell packaging machine for sealing. 2) Positive electrode (VO2(B))-zinc battery: Place the zinc sheet, glass fiber separator, positive electrode sheet, and stainless steel sheet (SS) in the CR2032 negative electrode battery shell in sequence, then put the spring sheet on, cover the CR2032 positive electrode battery shell, and put it into a button cell packaging machine for sealing. When sealing, the packaging pressure of the button cell packaging machine must be greater than 50kg / cm 3 , duration 10s. When encapsulating the positive electrode (VO2(B))-zinc battery, paper needs to be placed on top of the battery to prevent the formation of a circuit outside the battery during encapsulation. The newly encapsulated battery cannot be used immediately and needs to be left to stand for more than 2h to allow the electrode / electrolyte interface to fully contact before testing.

[0030] Example 2

[0031] Analysis and testing of the working state of aqueous zinc-ion batteries

[0032] The button cell prepared in Example 1 was placed in the Xinwei battery test system and tested at 0.5 A·g -1 Constant current cycle, test after 30 cycles.

[0033] There is no need to suspend the normal operation of the battery. A trace amount of electrolyte is diluted 80 times, and the content of Zn and V elements in the diluted electrolyte is tested by inductively coupled plasma mass spectrometer (ICP-MS). The average test is 3 times, and the relative standard deviation (RSD) of the six concentration data obtained is calculated. The result is considered to be accurate when the RSD is less than 1%. The test results of the electrolyte of the aqueous zinc ion battery in the working state by inductively coupled plasma mass spectrometer (ICP-MS) are shown in Table 1.

[0034] Table 1: Test results of the electrolyte of aqueous zinc ion battery in working state by inductively coupled plasma mass spectrometry (ICP-MS)

[0035]

[0036]

[0037] From Table 1, we can see that by converting the percentage of dissolved amount, we can get Zn 2+ The concentration is 1.018 mol·L -1 , indicating that some Zn in the negative electrode is dissolved in the electrolyte, but it is within the normal range. By converting the percentage of dissolved amount, the dissolved amount of V is 43.68μg·L -1 This indicates that some vanadium dioxide in the positive electrode is dissolved in the electrolyte, but the content is small and does not affect the normal operation of the aqueous zinc ion battery.

[0038] The TOF-SIMS negative ion mode was used to sputter Cs atoms with a sputtering energy of 1 KeV 80 nA and receive Bi3 ++ , the receiving energy is 30KeV, the receiving fragment range is 2-1000u, the length and width of the positive electrode is 50μm×50μm, and the depth is 200nm. The effective material on the positive electrode surface is tested and the compound fragment count is obtained.

[0039] The test results are as follows Figure 1-Figure 4 As shown, Figure 1 For all fragment spectra obtained by TOF-SIMS testing, Figure 2 This is the total count of all fragments obtained by TOF-SIMS testing. Figure 3 This is a graph showing the content variation of the four ion fragments of ZnO-, OH-, VO-, and ZnF2- with the depth of the sample. Figure 4 This is a 3D schematic diagram of the distribution of the four ion fragments ZnO-, OH-, VO-, and ZnF2- drawn using 3Dmax. Figure 1-Figure 4 It can be seen that the positive electrode of the aqueous zinc ion battery VO2(B) has Zn 2+ and H + The percentage of VO2(B) fragments is higher with the increase of the longitudinal depth, and it decreases sharply with the depth, indicating that the electrolyte salt Zn(OTf)2 is severely decomposed on the surface.

[0040] The above is only a preferred specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.

Claims

1. A method for analyzing the working state of an aqueous zinc ion battery, characterized in that: The steps include: S1, performing electrolyte analysis and positive electrode analysis on the aqueous zinc ion battery to be tested at the same time; wherein, the electrolyte of the aqueous zinc ion battery in a working state is analyzed by an inductively coupled plasma mass spectrometer to obtain an electrolyte analysis result; and the positive electrode of the aqueous zinc ion battery in a working state is analyzed by a time-of-flight secondary ion mass spectrometer to obtain a positive electrode analysis result; S2. Combine the electrolyte analysis results and the positive electrode analysis results to comprehensively detect the working status of the aqueous zinc ion battery in real time, and analyze the test results.

2. A method for analyzing the working state of an aqueous zinc ion battery as claimed in claim 1, characterized in that: In step S1, an inductively coupled plasma mass spectrometer is used to instantly detect the element content of the electrolyte during the operation of the aqueous zinc ion battery. The detected elements include one or more of Zn, Mn, V, Fe, P and S.

3. A method for analyzing the working state of an aqueous zinc ion battery as claimed in claim 1, characterized in that: In step S1, a time-of-flight secondary ion mass spectrometer is used to instantly detect ion fragments generated by the positive electrode of the aqueous zinc ion battery in operation, and the detected ion fragments include ion fragments of the positive electrode used and by-product ion fragments.

4. A method for analyzing the working state of an aqueous zinc ion battery as claimed in claim 2, characterized in that: In step S1, before using the inductively coupled plasma mass spectrometer for detection, if the electrolyte is an organic electrolyte or a mixed electrolyte, the electrolyte is first diluted with pure water until the proportion of organic components is less than 10%; if the metal element content in the electrolyte is greater than the threshold, the sample concentration is diluted between 1 and 10 ppm to improve the test sensitivity.

5. A method for analyzing the working state of an aqueous zinc ion battery as claimed in claim 1, characterized in that: The specific process of step S2 is: compare and analyze the electrolyte analysis results and the positive electrode analysis results. If the content of the main elements of the positive electrode active material in the electrolyte is greater than the threshold value, and the rate at which the percentage of the main ion fragments of the positive electrode active material decreases with depth is greater than the threshold value, it means that the positive electrode has a high solubility in the electrolyte during the electrochemical process and has a poor recovery ability after a charge and discharge cycle. Otherwise, it means that the positive electrode has a high solubility in the electrolyte and a good recovery ability. If there are non-initial positive electrode component ion fragments in the positive electrode, it means that there is Zn in the electrochemical work. 2+ and H + The greater the longitudinal depth, the higher the proportion of VO2(B) fragments, indicating that the effective active substances are better maintained; if the percentage of fragments of electrolyte components is high on the surface and the rate of increase with depth is less than the threshold, it means that the electrolyte salt is severely decomposed on the surface.

Citation Information

Patent Citations

  • Comprehensive evaluation method and system for thermal runaway safety of power battery

    CN110095722A

  • Capacity attenuation analysis method and apparatus, electronic device and storage medium

    CN110888079A

  • Device for testing electrochemical performance of battery related material

    CN111413389A

  • Secondary battery and device

    CN116454394A

  • Analysis method and analysis system for battery containing liquid electrolyte

    CN118310918A